PENERAPAN SISTEM ZONASI OLEH DINAS PENDIDIKAN DALAM PENERIMAAN PESERTA DIDIK BARU DI SMP NEGERI 1 DAN SMP NEGERI 2 PANGKALAN KERINCI KABUPATEN PELALAWAN TAHUN 2019/2020 - Liza, Hanindatul; ", Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Zoning system is a new student admission system that is enforced with the determination of zone radius by the respective local government and schools must accept prospective students who live in the nearest zone radius with a certain percentage of the total number of students to be accepted. The zoning system quota is 80% of the capacity, the achievement path is 15% of the capacity and the parent/guardian transfer path is at most 5% of the capacity. The new zoning system was implemented by the Pelalawan District Education Office in the 2019/2020 school year.The purpose of this research is to find out how the Zoning System is implemented by the Pelalawan District Education Office in two different schools. The research locations are in Pelalawan District Education at SMP Negeri 1 Pangkalan Kerinci. This research uses qualitative research. This type of research is descriptive. Data were collected through informants purposively. Data collection techniques using interviews, documentation and documents            `The result showed that the zoning system is implemented By Pelalawan District Education Office at SMP Negeri 1 Pangkalan Kerinci was still not optimal. The excessive power that exceeds the limit, the lack of information regarding PPDB through the zoning system, the lack of communication that occurs between the Education Office, schools and the community. Lack of  socialization carried out by the Pelalawan District Education Office in application of zoning. Keywords: Zoning System, Implementation, PPDB